Shunting, optic nerve sheath fenestration and dural venous stenting for medically refractory idiopathic intracranial hypertension: systematic review and meta-analysis - Scherman, Daniel B.; Dmytriw, Adam A.; Nguyen, Gia Thanh; Nguyen, Nhan Thi; Tchantchaleishvili, Nana; Maingard, Julian; Asadi, Hamed; Brooks, Mark; Griessenauer, Christoph; Ogilvy, Christopher; Thomas, Ajith J.; Moore, Justin M.; et al. (Annals of Eye Science, 2018)
Background: Cerebrospinal fluid (CSF)-diversion procedures have traditionally been the standard of treatment for patients with medically refractive idiopathic intracranial hypertension (IIH). However, dural venous sinus stent (VSS) placement has been described as a safe and effective procedure for the management of medically refractive IIH. We performed a meta-analysis comparing outcomes and complications of CSF-diversion procedures, VSS and optic nerve sheath fenestration (ONSF) for the treatment of medically refractive IIH. Methods: Electronic searches were performed using six databases from 1988 to January 2017. Data was extracted and meta-analysed from the identified studies. Results: From 55 pooled studies, there were 538 CSF-diversion cases, 224 dural venous stent placements, and 872 ONSF procedures. Similar improvements were found in terms of postoperative headaches (CSF vs. VSS vs. ONSF: 84% vs. 78% vs. 62%, P=0.223), papilledema (CSF vs. VSS vs. ONSF: 71% vs. 86% vs. 77%, P=0.192), whilst visual acuity changes favored venous stenting (CSF vs. VSS vs. ONSF: 55% vs. 69% vs. 44%, P=0.037). There was a significantly lower rate of subsequent procedures with venous stent placement (CSF vs. VSS vs. ONSF: 37% vs. 13% vs. 18%, P